Comparative Study of the Skeletal Structures of Pagrus pagrus and P. caeruleostictus in the Eastern Libyan Coast - Randah A. Ahmed; Najiyah S. Husayn; Doaa A. Alattar (African Journal of Advanced Pure and Applied Sciences, 2024)
This study provides a detailed comparative analysis of the skeletal structures of two closely related species, common red sea bream, Pagrus pagrus, and blue-spotted Pagrus caeruleostictus, found along the eastern Libyan coast. One hundred fifty fish (75 from each species) were acquired from the eastern Libyan coast to examine the skeletal traits. Morphometric, skeletal traits such as the cranium, vertebral column, and fin girdles were examined to explore potential morphological differences linked to ecological niches, behavior, and evolutionary adaptations. Results reveal significant differences, with P. caeruleostictus exhibiting larger body size, longer fins, and greater cranial dimensions than P. pagrus. Specific skeletal traits, such as vertebral centrum diameter and glenoid fossa depth, further differentiate the species, highlighting adaptations to their respective habitats. Statistical analysis confirmed significant interspecies variations in most parameters (p < 0.05), emphasizing ecological and functional adaptations. These findings provide insights into these species’ ecological roles and habitat preferences, offering critical information for the region’s biodiversity conservation and sustainable fisheries management.